Simulação e ensaio de mecanismo de freio automotivo - Rafael Martins de Abreu (2013)
With the increase of vehicles power, the security systems must to keep updated to meet the new requirements. The propose of this study was to build a test bench to make possible simulate brakings with different kinds of disc pads and changing some parameters. To be possible to control and evaluate interferences of this parameters in the phenomenon of braking, the test bench was instrumented and monitored, enabling the compilation of data related to determined pairs of disc pads and brake disks. The tests were made using three kinds of disc pads, two new of different manufactures and one used. The basis of the tests was shaped second test criteria Krauss, regulated by ABNT NBR 6143:1995 and it were added cycles of tests to make possible detect the parameters interference of disc pads actuation force and different speeds. It were monitored the behavior of braking, relationated to its effectiveness in stop the brake disc, the levels of accoustic emission in each cycle, the temperature during the tests and the loss of mass of disc pads, controling the actuation force using a pneumatic cylinder and controling rotation using a frequence inversor. Also used to FEA for a brief comparison of the results with the virtual and physical.